Radial pseudoaneurysm following diagnostic coronary angiography - Laudari, Shankar; Dhungel, Sachin; Dubey, Laxman; Prasad, Guru; Bhattacharya, R; Subramanyam, S (Journal of College of Medical Sciences-Nepal, 2015)
The radial artery access has gained popularity as a method of diagnostic coronary catheterization compared to femoral artery puncture in terms of vascular complications and early ambulation. However, very rare complication like radial artery pseudoaneurysm may occur following cardiac catheterization which may give rise to serious consequences. Here, we report a patient with radial pseudoaneurysm following diagnostic coronary angiography. Adequate and correct methodology of compression of radial artery following puncture for maintaining hemostasis is the key to prevention. DOI: http://dx.doi.org/10.3126/jcmsn.v10i3.12776 Journal of College of Medical Sciences-Nepal, 2014, Vol-10, No-3, 48-50